2020
DOI: 10.1007/s00125-020-05310-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of cardiac autonomic dysfunction with higher levels of plasma lipid metabolites in recent-onset type 2 diabetes

Abstract: Aims/hypothesis Emerging evidence suggests that in addition to hyperglycaemia, dyslipidaemia could represent a contributing pathogenetic factor to diabetic neuropathy, while obesity and insulin resistance play a role in the development of diabetic cardiac autonomic neuropathy (CAN) characterised by reduced heart rate variability (HRV), particularly in type 2 diabetes. We hypothesised that distinct lipid metabolites are associated with diminished HRV in recent-onset type 2 diabetes rather than type 1 diabetes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 44 publications
(58 reference statements)
1
21
0
1
Order By: Relevance
“… 33 Several phosphatidylcholines and sphingomyelins correlated inversely with cardiac autonomic neuropathy in participants with type 2, but not type 1, diabetes, concluding this may arise from dyslipidemia as a major driver of nerve damage secondary to type 2 diabetes. 33 …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“… 33 Several phosphatidylcholines and sphingomyelins correlated inversely with cardiac autonomic neuropathy in participants with type 2, but not type 1, diabetes, concluding this may arise from dyslipidemia as a major driver of nerve damage secondary to type 2 diabetes. 33 …”
Section: Discussionmentioning
confidence: 92%
“…33 Several phosphatidylcholines and sphingomyelins correlated inversely with cardiac autonomic neuropathy in participants with type 2, but not type 1, diabetes, concluding this may arise from dyslipidemia as a major driver of nerve damage secondary to type 2 diabetes. 33 We have also reported lipidomic analyses of other diabetic complications in the Pimas, including nephropathy 13 and retinopathy. 34 The neuropathy lipidomic signatures from the current study were distinct to both the DKD and the retinopathy signatures, although signatures in all three diabetic complications centered around impaired boxidation.…”
Section: Discussionmentioning
confidence: 92%
“…Glycerophospholipid, and sphingolipid accumulation in cerebrospinal fluid (CSF) [36] and plasma [37] have shown an increased lipid turnover in subjects with Alzheimer's disease (AD) consistent with the formation of inflammatory lipids [38][39][40][41][42]. Similar changes in inflammatory lipid species have also been found in Parkinson's disease [43] and Multiple sclerosis [44], as well as metabolic diseases such as type 2 diabetes [45], non-alcoholic steatohepatitis [46] and non-alcoholic fatty liver [47] where liver biopsies and high serum levels of sphingomyelins have been used as biomarkers of visceral adipose tissue and hepatic triglyceride content [47,48]. A protective association between metabolites reflecting the consumption of mushroom and brain health have been proposed in a prospective cognitive decline study with humans [18] and after oral administration of the mushroom derived antioxidant ergothioneine in a recognition memory study in rodents [17].…”
Section: Discussionmentioning
confidence: 79%
“…In crude analyses we found CAN to be associated with lower levels of phosphatidylcholine 38:6 and 32:0 and the E/I ratio the proportionally associated with phosphatidylcholine 34:3. Recently, opposite associations were found in persons with recent onset type 2 diabetes ( 36 ), where more pathological measures of autonomic dysfunction by HRV were associated with higher levels of several phosphatidylcholines including 32:0. The same study examined persons with recent onset type 1 diabetes and found no associations between CAN and lipid compounds.…”
Section: Discussionmentioning
confidence: 96%